PENGARUH TRANSAKSI NON TUNAI TERHADAP JUMLAH UANG BEREDAR DENGAN INFLASI SEBAGAI VARIABEL MODERASI - Shinta Ainur Rahmadani; Nurma Yunita; Aprika Wanti Pratama; Maya Panorama (STIE PGRI Dewantara Jombang, 2022)
Non-cash transactions in monetary policy affect the level of money circulating in society. In addition, another factor that affects the amount of money in circulation is inflation. Non-cash transactions in this study use Debt non card transaction, Credit non card transaction, and electronic money (e-money). This study aimed to determine the effect of non-cash transactions on the money supply in Indonesia with inflation as a moderating variable during 2019-2021. The research uses secondary data and the analysis technique used is multiple linear regression analysis and the Moderating Regression Analysis (MRA) test. The results of the study state that non-cash transactions have a partially and simultaneously significant effect on the money supply and that inflation can strengthen the relationship between non-cash transactions and the money supply.